2012
DOI: 10.2478/s13382-012-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to orthopedic metal implants — A prospective study

Abstract: Objectives: Evaluation of the allergenic properties of the metal knee or hip joint implants 24 months post surgery and assessment of the relation between allergy to metals and metal implants failure. Materials and Methods: The study was conducted in two stages. Stage I (pre-implantation) -60 patients scheduled for arthroplasty surgery. Personal interview, dermatological examination and patch testing with 0.5% potassium dichromate, 1.0% cobalt chloride, 5.0% nickel sulfate, 2.0% copper sulfate, 2.0% palladium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 24 publications
0
61
0
Order By: Relevance
“…5 The efficacy of patch testing for allergies to metal in orthopaedic patients has been debated. 6,7 In a review, Thyssen et al 8 concluded that clinicians refrain from wholesale patch testing. One of the key points in their argument was that of cost-benefit.…”
Section: Discussionmentioning
confidence: 98%
“…5 The efficacy of patch testing for allergies to metal in orthopaedic patients has been debated. 6,7 In a review, Thyssen et al 8 concluded that clinicians refrain from wholesale patch testing. One of the key points in their argument was that of cost-benefit.…”
Section: Discussionmentioning
confidence: 98%
“…In the field of orthopedics, metal orthopedic implants are considered to be the primary cause of allergies that may lead to implant failure [4,5,17]. Patch test screening has increasingly been suggested to be obligatory prior to orthopedic metal implant insertion in patients reporting symptoms of metal dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of orthopedics, metal orthopedic implants have been implicated as the primary cause of allergies that may lead to implant failure. Kręcisz et al [5] insisted that patch test screening should be obligatory prior to implanting these devices into patients reporting symptoms of metal dermatitis and that patients with confirmed allergies to metals should be provided with implants without allergenic metals. Although anecdotal reports have chronicled side effects, such as pericarditis, chest discomfort, migraine headache and ASD occluder embolization leading to device removal after intracardiac device implantation [2,6,7,8], some authors reported successful transcatheter closure even in patients with symptomatic nickel allergy, suggesting that nickel allergy per se is not a contraindication to ASD closure with a nitinol device; however, these contradictory results and concerns about the safety associated with long-term effects of implants underscore the value of post-implantation surveillance studies.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the probability of developing a metal allergy was higher after surgery (OR, 1.52; 95%CI, 1.06-2.31) and that the risk was even higher when failed implants were compared with stable total joint replacements (OR, 2.76; 95%CI, 1.14-6.70) [25]. A few recent prospective studies have also suggested an increase in cases of metal allergy following THA, even in patients with well-functioning prostheses [26][27][28].…”
Section: The Rising Potential Impact Of Metal Hypersensitivitymentioning
confidence: 99%
“…Stainless steel, which contains a large percentage of nickel, is often used for screws while cobalt-chromium alloy, which has approximately 1% nickel content, is often used in total joint arthroplasty [9,32]. Metal hypersensitivity has long been studied as a potential cause of complications after total joint arthroplasty, ever since the first case of metal-related dermatitis was first reported in 1966 [33][34][35][36][37]. Cutaneous manifestations of suspected metal hypersensitivity reactions can include localized and generalized eruptions in the form of erythema, urticaria, and vasculitis, and such manifestations can be observed with static implants, dynamic joint prostheses, and, occasionally, in the implants used in TKA [16,[38][39][40][41][42][43].…”
Section: Orthopedic Implantsmentioning
confidence: 99%